Application of Inquiry Collaborative Constructivism Model in Biology Learning Respiratory System to Improve Students' Critical Thinking Skills - Dewi Cahyani; Filia Yunita; Mujib Ubaidillah (JURNAL PENDIDIKAN SAINS (JPS), 2022)
Currently all alternatives to meet the needs of life in various contexts are based on knowledge. Developing critical thinking skills is an important aspect of academic studies. Inquiry-based learning is a contextual learning model that can make students participate actively during learning. The purpose of this study was to review the effectiveness of the application of the inquiry-collaborating constructivism model in biology learning. The type of research conducted was a quantitative approach through pre-experimental methods. The design of this research was One-group pre-test-post-test design. This research was carried out at SMAN 1 Jamblang precisely in class XI MIPA in the even semester of the 2019-2020 school year. The instruments used were observation sheets and test questions. The results of the average value of the student activity showed results with very good criteria for each meeting. Based on the hypothesis test, it was known that the 2-tailed significance was < 0.05. This indicated that there was a significant difference between the pre-test and post-test scores after the application of the inquiry-collaborating constructivism learning model. The application of the inquiry-collaborating constructivism model was considered effective in improving students' critical thinking skills.